Between Normative Guarantees and Empirical Realities: Disability Access to Marriage Services at Religious Affairs Offices in Surabaya - Shodiqin, Mohammad; Ghufron, Muhammad; Bilhaq, Ahmad Razan (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2025)
The state bears a constitutional obligation to ensure equal access to public services, including marriage registration, for all citizens, including people with disabilities. However, in practice, the accessibility of marriage services at the Office of Religious Affairs (KUA) remains limited. This study aims to examine the inclusivity of marriage services for people with disabilities at four KUAs in Surabaya: Tambaksari, Sawahan, Semampir, and Wonokromo. Using a sociological jurisprudence design, this empirical study collected data through observation and in-depth interviews with KUA heads and penghulus (marriage registrars). The findings reveal significant disparities in physical and non-physical accessibility, with only the Sawahan KUA demonstrating minimal infrastructure readiness. Other KUAs still face structural barriers, a lack of assistive facilities, and the absence of sign language interpreters. In response, marriage registrars employ discretionary practices, such as non-verbal consent mechanisms and family-assisted communication, as survival innovations to ensure the validity of marriage procedures. However, these practices remain partial and non-standardized, potentially leading to legal uncertainty and unequal access to services. From a human rights and Islamic law perspective, these limitations reflect a gap between normative guarantees and empirical reality, particularly regarding the fulfillment of the principles of equality and non-discrimination. This study advocates a paradigm shift from a charitable to a rights-based approach, ideally supported by technical regulations, inclusive infrastructure, and institutional capacity-building, to ensure dignified and equal access to marriage services for persons with disabilities.